What kind of Corporation Tax Regime? - Sijbren Cnossen (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper explores the taxation of corporations in the wider context of capital income taxation. The pros and cons of various income-based and cash-flow forms of corporation tax (CT) are discussed. The paper concludes that the dual income tax (DIT), which taxes all capital income at the proportional CT rate, is to be preferred over other forms of taxing capital income. The DIT is best attuned to the reality of capital mobility and is not held hostage by the higher tax on labour income. Levied at a uniform flat rate, the DIT minimizes opportunities for tax arbitrage.
Keywords: G30; H24; H25; 330; comprehensive business income tax; corporation tax; dividend relief systems; dual income tax; flat tax; cash flow taxation